Função social da empresa e a responsabilidade social empresarial como fator determinante para um novo modelo de atividade empresarial - Becker, Joseane Isabel (2021)
Business activity is analyzed based on the principles of economic order provided for in the Federal Constitution of 1988, as a way of extracting the effectiveness of the company's social function and social responsibility. The balance between the company's profitable activity, social and environmental aspects related to business activity are analyzed in order to present a proposal aimed at its regulation, as a true public policy in Brazil. To achieve this objective, initially the company's historical and legal aspects will be presented, based on the related constitutional principles and, especially, with regard to the new conception of Corporate Law. Also, the company will be approached in the Brazilian economic and social order, revealing the general principles of economic activity that guide its operations, as well as the mechanisms that must be activated for the company to act in order to guarantee respect for the dignity of the human person. . The research question is related to the need for a contemporary conception of the company, from which it is no longer accepted a corporate culture that privileges only profit, but that also takes into consideration ethical values and, mainly, the dignity of the human person. . All analysis will be based on the constitutional fundamentals and principles of the economic order, with an emphasis on the social function of the company, as well as the analysis of business performance in its legal, economic and social aspects. The company that aims to fulfill its social function must adopt an ethical, transparent and committed posture not only with the legal obligations, positivized in the article 170 of the CF and in the labor, environmental and consumerist norms, but go beyond, since it does not find limit in the Existing legislation to seek to realize people's social rights, especially because it will not be only through positive norms that the effective regulation of business activity will take place. The great challenge to the legal system is that the regulation of business activity, even considering competitive markets, does not prioritize only profit, but integrates its actions with the objective of simultaneously meeting social, economic and environmental values, essential elements in what was agreed call sustainability tripod. Growth and sustainable economic development are linked to business activities that are also concerned with social and environmental issues, in order to achieve the expected balance, with a view to social interests, greater dignity to people, material equality and social justice, objectives desired by the Brazilian legal system, as the Constitution chapter related to the economic order provides.